The relationship between learning independence and PISA test result scores - Deyjan Ahsan Nur Rijal; Dini Fitriani (Pi Radian: Journal of Mathematics Education, 2023)
Mathematics is a mandatory subject that students need to master, but many still think it is not related to life. This is evidenced by the fact that Indonesia's PISA score is below the average. The test results themselves are usually related to and can be influenced by learning discipline that coincides with learning independence, but can learning independence alone have a significant effect on test results. This study aims to see a relationship between learning independence and the results of the PISA test at SMP Plus Nurul Hidayah Pasundan. This was done by collecting data in the form of PISA test results and self-learning questionnaires. With several tests carried out, it is proven that independent learning can influence the results of the PISA test questions with a significance value of 0.000011335039557777 with the interpretation that there is a positive and significant relationship. The strength of the influence caused by independent learning is at 78.4%, meaning that independent learning greatly influences the results of the PISA test questions.